2006
DOI: 10.2334/josnusd.48.71
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Piper betle and Psidium guajava extracts on the cell-surface hydrophobicity of selected early settlers of dental plaque

Abstract: The adhesion of early settlers of dental plaque to the tooth surface has a role in the initiation of the development of dental plaque. The hydrophobic surface properties of the bacteria cell wall are indirectly responsible for the adhesion of the bacteria cell to the acquired pellicle on the tooth surfaces. In this study, the effect of aqueous extract of two plants (Psidium guajava and Piper betle) on the cell-surface hydro-phobicity of early settlers of dental plaque was determined in vitro. Hexadecane, a hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 19 publications
(24 reference statements)
2
39
0
2
Order By: Relevance
“…In vitro studies have shown the potential of Psidiumguajava in disrupting the bonding and adhesion of early settlers in dental plaque [3,21].Its capacity to act against the chief cariogenic pathogen S.mutans and the common periodontal bacteria P.intermedia was demonstrated in this study. Moreover, it showed no potential against Candida and P.gingivalis.…”
Section: Discussionmentioning
confidence: 80%
“…In vitro studies have shown the potential of Psidiumguajava in disrupting the bonding and adhesion of early settlers in dental plaque [3,21].Its capacity to act against the chief cariogenic pathogen S.mutans and the common periodontal bacteria P.intermedia was demonstrated in this study. Moreover, it showed no potential against Candida and P.gingivalis.…”
Section: Discussionmentioning
confidence: 80%
“…Any strategy responsible for reducing the cell surface hydrophobicity and EPS synthesis may affect the development of infection, making the cells more susceptible to antibiotics. A previous study also reported that some plant extracts inhibit the biofilm-forming capacity of Gram-positive and Gramnegative bacteria by interfering with their hydrophobicity (Annuk et al, 1999;Nostro et al, 2004;Razak et al, 2006). P. aeruginosa and S. aureus infections are difficult to eradicate because of their resistance to many antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface charge and CSH play a crucial role in bacterium-host cell interactions [26]. There are several reports regarding plant extracts interfering in the biofilm formation of Gram-negative bacteria [27] and Gram-positive bacteria [28][29][30]. Biofilm-associated diseases caused by Gram-positive bacteria include caries, gingivitis, periodontitis, endocarditis and prostatitis [31].…”
Section: Resultsmentioning
confidence: 99%